Separation characteristics of an integrated temperature-controlled micro gas chromatography chip. (15th March 2021) - Chen, J.L.; Han, B.Q.; Liu, T.H.; Wang, H.R.; Wang, J.H.
Abstract: Compared with traditional laboratory gas chromatograph, portable gas chromatograph has the advantages of fast detection, low power consumption, lost cost and possible applications out of Lab. In this paper, aiming at replacing the traditional column thermostat, we presented a 4 cm · 4 cm micro gas chromatography (μGC) chip with a thickness of about 1 mm and a column length of 3 m integrating the Pt heating wire and snake-shaped temperature sensor, which greatly reduces the power consumption and volume of the portable gas chromatograph without losing the separation performance of the μGC chip. The integrated μGC chip was fabricated by micro electro mechanical systems (MEMS) process and its temperature was controlled in closed-loop by fuzzy proportion integration differentiation (PID) algorithm. Experimental results indicate the temperature control accuracy under constant temperature can be up to ±0.05 °C. When heating to 180 °C, the power consumption is less than 15 W. The chip has good separation properties when it was used to detect 4 kinds of benzenes, 8 kinds of alcohol mixtures and 10 kinds of alkane mixtures.